The baseball trust : a history of baseball's antitrust exemption - Banner, Stuart, 1963- (Oxford Univ Press, 2013)
The impact of antitrust law on sports is in the news all the time, especially when there is labour conflict between players and owners, or when a team wants to move to a new city. And if the majority of Americans have only the vaguest sense of what antitrust law is, most know one thing about it - that baseball is exempt. This book illuminates the series of court rulings that resulted in one of the most curious features of the US legal system: baseball's exemption from antitrust law.